2016
DOI: 10.3109/07434618.2016.1146331
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Effects of Interventions to Promote Peer Interactions for Children who use Aided AAC

Abstract: The goals of this systematic review were to investigate studies that implemented interventions to increase or improve peer interaction for children who used aided AAC, to evaluate the strengths and limitations of those studies, and to discuss implications for practice and directions for future research. A systematic search resulted in the identification of 19 studies (56 participants). Studies were coded and summarized in terms of participants, independent and dependent variables, outcomes, and quality of evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 39 publications
0
26
0
2
Order By: Relevance
“…Recent reviews on AAC intervention studies report limitations related to the need for (a) a larger number of children and randomized group designs, (b) measuring outcomes with different communication partners, and (c) reporting generalization across settings and partners and if progress is maintained (Therrien et al, 2016;van der Meer & Rispoli, 2010). In the PMI literature, there is a need for research on (a) preschool-age children, (b) a larger number of participants, (c) generalization and maintenance measures, (d) treatment fidelity data for peer behaviors, and (e) social validity outcomes (Zagona & Mastergeorge, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reviews on AAC intervention studies report limitations related to the need for (a) a larger number of children and randomized group designs, (b) measuring outcomes with different communication partners, and (c) reporting generalization across settings and partners and if progress is maintained (Therrien et al, 2016;van der Meer & Rispoli, 2010). In the PMI literature, there is a need for research on (a) preschool-age children, (b) a larger number of participants, (c) generalization and maintenance measures, (d) treatment fidelity data for peer behaviors, and (e) social validity outcomes (Zagona & Mastergeorge, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Research on strategies to teach peers to be communication partners for individuals with developmental disabilities learning to use AAC is growing for elementary and secondary students (Chung, Carter, & Sisco, 2012b). Therrien, Light, and Pope (2016) reported that, of 19 AAC studies designed to improve peer interactions, only 30% included participants with autism and that six of these were preschool children with complex communication needs (within two single-subject design studies). Overall, the authors reported higher gain scores on peer interaction skills in studies that combined approaches, such as peer training (e.g., peers taught to model or prompt AAC use), child-specific instruction on AAC use, and arranging the environment.…”
Section: Aac Interventions and Peer Partnersmentioning
confidence: 99%
“…Other intervention models suggest embedding JA interactions into pretend play contexts [3]. Therapy approaches which focus on combining social interaction with direct training will lead to increases in skills of initiating and maintaining JA with others for children with ASD [20].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence supports the benefits of integrating peer-mediated approaches into AAC interventions for children with complex communication needs (Thiemann-Bourque et al, 2018). A recent review summarizing 19 AAC intervention studies designed to promote peer interactions concluded that a multimethod approach may be most effective in supporting and improving peer interactions for this population (Therrien, Light, & Pope, 2016). Methods to enhance communication include teaching specific communication skills during AAC instruction, teaching peers to be responsive partners, and setting up a supportive environment.…”
Section: Aac Interventions and Peer Partnersmentioning
confidence: 99%